Evaluación presupuestaria al Gobierno Autónomo Descentralizado Municipal del Cantón Yantzaza de la Provincia de Zamora Chinchipe período 2011 - Romero Rojas, Ruth Elizabeth (2016)
The present thesis entitled "GOVERNMENT BUDGET SELF ASSESSMENT DECENTRALI Yantzaza CANTON CITY OF THE PROVINCE OF ZAMORA CHINCHIPE PERIOD 2011" was carried out in compliance with the requirement before the degree of Engineer opt in Accounting and Auditing Accountant, Public-Auditor. To implement the first specific objective was taken into consideration the initial budget for 2011 and the Annual Operating Plan (AOP) to implement indicators and check if all your projects and results were achieved. For the second objective indicators applied different budget, so verify the efficiency and effectiveness of the administrative part when preparing the initial budget of the Autonomous Decentralized Yantzaza Canton in the period 2011, sourced the Annual Operating Plan (POA). For the third objective, we proceeded to perform the Annual Indicative Programming (IAP) Quarterly Programming Commitment (PCC), Initial Budget, Corporate Budget Modified (PIM), Cedulas Budget and Budget Execution State Decentralized Autonomous Municipal Government Canton Yantzaza same who served in the application of indicators to thereby check whether the budget was executed with efficiency, effectiveness effectiveness. To fulfill the fourth specific objective Mayor reported Decentralized Autonomous Municipal Government of Guangzhou Yantzaza with the results obtained in the evaluation budget that allows correct and appropriate decisions to improve the resources available to the Municipality; thus complying to each of the initial objectives of this thesis work. The methodology used was the Scientific Method, Inductive, Deductive, Analytic, and mathematician who helped the implementation and development of the objectives in this thesis work. In the end it presents the conclusions and recommendations as a basis for the Government of the Canton Municipal Autonomous Decentralized Yantzaza properly determine the resources allocated for sound decision-making.